Effet d'une supplementation de pailles de cereales avec de l'uree, du foin de Trifolium et du tourteau de noug sur l'ingestion et le gain ponderal de genisses hybrides - Olayiwole, M.B.; Butterworth, M.H.; Sayers, A.R.; Olorunju, S.A.S. (1986)
Compares the effects of noug meal, Trifolium tembense hay and urea, fed in different combinations as supplements to wheat or teff straws, on feed intake and growth rate of crossbred heifers.